Identifikasi Kemampuan Servis Peserta Ekstrakurikuler Bolavoli SMPI Nashirul Ummah Tuban - Rudianto, Agung; Herpandika, Reo Prasetiyo; Pratama, Budiman Agung (MAN Insan Cendekia Jambi, 2025)
This study aimed to identify volleyball service skills among 22 male extracurricular participants at SMPI Nashirul Ummah, Tuban Regency, East Java. Utilizing a quantitative descriptive method with total population sampling, the Russell-Lange Volleyball Service Test was administered. Data was analyzed using descriptive statistics and presented in tables, diagrams, and categories. Results revealed varied service abilities. Individual scores ranged from 18 to 35, with an average of 26.23 and a standard deviation of 5.15. Categorically, most participants (36.4%) fell into the 'Moderate' category, followed by 'Poor' (27.3%), 'Good' (22.7%), 'Very Poor' (9.1%), and only one student (4.5%) in 'Very Good'. This suggests that while most participants have basic understanding, optimal proficiency is lacking, indicating significant room for improvement. In conclusion, service skills at SMPI Nashirul Ummah are predominantly